Mapping the Potential of Bakas Tourism Village in Klungkung Regency Bali - Purnama Dewi, Desak Made; Darma Susila, I Made Gede; Satria Jaya, Sang Made Krisna (Akademi Komunitas MAPINDO, 2024)
Bakas Village, Banjarangkan District, Klungkung Regency, is one of the tourist villages in Klungkung Regency based on Klungkung Regent Regulation Number 2 of 2017 concerning the Establishment of Tourism Villages and Decree Number 82 of 2018 concerning the Establishment of the Bakas Village Tourism Awareness Group (POKDARWIS). Since being designated as a tourist village, the number of tourists visiting Bakas village every day is only 15 people, which is far from the target visit program launched by the Bakas Village Tourism Awareness Group of 2000 tourists visiting every month or approximately 66 tourists every day. The purpose of this research is to find out the right strategy in developing tourism in Bakas Village. The research was conducted using descriptive qualitative analysis with data collection techniques in the form of observation, documentation study and in-depth interviews. Based on the research analysis, it shows that the mapping of the potential of Bakas Tourism Village is very large, spelled out from diverse tourism products ranging from natural, cultural, and artificial tourism attraction products, especially the concept of community-faced tourism, supported by supporting facilities and adequate access routes. The obstacles faced by Bakas Tourism Village in marketing are the lack of adequate human resources to carry out marketing systems, especially when promoting on social media, and there is uncertainty in the price of each Bakas village tourism product. Keyword: Tourism Potential, Tourism Attractions, Tourism Village, Bakas Village